The Entreprenuerial Marketing: Concept, Nature And Orientations - Hongal, Prof. Pushpa; Ramanjaneyalu, Dr. N.; Phatak, Dr. Gururaj (International Journal of Scientific Research and Management (IJSRM), 2022)
Entrepreneurial Marketing is the old and untouched, unfocussed Entrepreneurship and Marketing topic. Its research is has started around 30 years old. The purpose of this paper is to discuss the Evolution and the Nature of Entrepreneurial Marketing, Historical perspective of the Evolution of EM and Six core dimensions of entrepreneurial marketing are identified. The Research aims to focus on the Marketing Orientation as well as Entrepreneurial Orientations in Venture Creation and Management. A comprehensive assessment of the most representative publications from worldwide marketing and entrepreneurial journals was employed in this conceptual study. This study provides a brief overview of the evolution of EM as well as an examination of the most frequent definitions. Insights are drawn from a variety of sources, including corporate entrepreneurship, innovation and new product creation, creative leadership, and change management research. Entrepreneurial marketing's intellectual substance and validity are assessed. Priorities for future study are offered, as well as consequences for theory development, training, and management practice